Why did they get in trouble? The influence of firm characteristics and institutional distance on Chinese firms’ foreign market entry attempt - Zhang, Shuo (Frontiers in Psychology, 2022)
Despite the rich body of research on the outward foreign direct investment (OFDI) by Chinese multinationals, little attention has been given to the fact that China’s outward foreign direct investment is facing a high failure rate even in their initial attempt to enter a foreign market. Grounded on institutional theory, this study provides a nuanced view of the expansion dynamic of Chinese multinational firms’ overseas using a unique dataset that contains both successful and troubled Chinese foreign market entry attempts between 2018 and 2021. We find that at the firm level, state-owned firms are more likely to face difficulties when trying to enter a new market compared to their private counterparts. Firms’ corporate social responsibility reporting reduces the chance of failure. These effects are conditioned on the political, economic, and cultural distances between the home and host counties.